(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
As a result of pneumosclerosis, severe heart failure occurs in the body. The development of this heart failure is a long-term fatigue of the myocardium due to overwork, which is explained by the outflow of blood from the heart into the large vessels (overwork fatigue) or as a result of an excessive increase in blood flow to the heart. Pulmonary fibrosis is a chronic pathology that develops continuously. The purpose of the work was to determine the results and collect data on the morphological and morphometric changes in the hearts of white rats with pulmonary fibrosis under experimental conditions.